High sensitivity and low detection limit sensor based on a slotted nanobeam cavity - Al-Hmoud, Mohannad; Alyahyan, Rasha (Photonics Letters of Poland, 2022)
In this work, the three-dimensional finite-difference time-domain (3D-FDTD) method is used to design and analyze a refractive index sensor based on a slotted photonic crystal nanobeam cavity. These type of cavities support a high quality-factor and a small volume, and therefore is attractive for optical sensing. We demonstrate that when immersing our proposed sensor in water it can possess a high-quality factor of 2.0×10^6, high sensitivity of 325 nm/RIU, and a detection limit of 2.4×10^(-7) RIU. We believe that our proposed sensor is a promising candidate for potential applications sensing like in optofluidic- and bio-sensing. Full Text: PDF References E. Chow, A. Grot, L. Mirkarimi, M. Sigalas, G. Girolami, "Ultracompact biochemical sensor built with two-dimensional photonic crystal microcavity", OSA Trends Opt. Photonics Ser. 97 909 (2004). CrossRef S. Kim, H-M. Kim, Y-H. Lee, "Single nanobeam optical sensor with a high Q-factor and high sensitivity", Opt. Lett. 40 5351 (2015). CrossRef D-Q, Yang, B Duan, X, Liu, A-Q, Wang, X-G, Li, Y-F, Ji, "Photonic Crystal Nanobeam Cavities for Nanoscale Optical Sensing: A Review", Micromachines 11 (2020). CrossRef P.B. Deotare, M.W. McCutcheon, I.W. Frank, M. Khan, M. Lončar, "High quality factor photonic crystal nanobeam cavities", Appl. Phys. Lett. 94 121106 (2009). CrossRef P. Seidler, K. Lister, U. Drechsler, J. Hofrichter, T. Stöferle, "Slotted photonic crystal nanobeam cavity with an ultrahigh quality factor-to-mode volume ratio", Opt. Express 21 32468 (2013). CrossRef H. Choi, M. Heuck, D. Englund, "Self-Similar Nanocavity Design with Ultrasmall Mode Volume for Single-Photon Nonlinearities", Phys. Rev. Lett. 118 223605 (2017). CrossRef M. Al-Hmoud, S. Bougouffa, "Simultaneous high Q/V-ratio and optimized far-field emission pattern in diamond slot-bridge nanobeam cavity", Results Phys. 26 104314 (2021). CrossRef Q. Quan (2014). CrossRef M.A. Butt, C. Tyszkiewicz, P. Karasiński, M. Zięba, D. Hlushchenko, T. Baraniecki, A. Kaźmierczak, R. Piramidowicz, M. Guzik, A. Bachmatiuk, "Development of a low-cost silica-titania optical platform for integrated photonics applications", Opt. Express 30 23678 (2022). CrossRef D-Q. Yang, B. Duan, X. Liu, A-Q. Wang, X-G. Li, Y-F. Ji, ""Photonic Crystal Nanobeam Cavities for Nanoscale Optical Sensing: A Review", Micromachines 72, 11 (2020). CrossRef Y.N. Zhang, Y. Zhao, R.Q Lv, "A review for optical sensors based on photonic crystal cavities", Sens. Actuators A: Phys. 233 374 (2015). CrossRef P. Lalanne, S. Mias, and J.P. Hugonin, "Two physical mechanisms for boosting the quality factor to cavity volume ratio of photonic crystal microcavities", Opt. Express 12 458 (2004). CrossRef C. Sauvan, G. Lecamp, P. Lalanne, J.P Hugonin, "Modal-reflectivity enhancement by geometry tuning in Photonic Crystal microcavities", Opt. Express 13 245 (2005). CrossRef J.T. Robinson, C. Manolatou, L. Chen, M. Lipson, "Ultrasmall Mode Volumes in Dielectric Optical Microcavities", Phys. Rev. Lett. 95 143901 (2005). CrossRef S. Olyaee, M. Seifouri, R. Karami, A. Mohebzadeh-Bahabady, "Designing low power and high contrast ratio all-optical NOT logic gate for using in optical integrated circuits", Opt. Quantum Electron. 51 1 (2019). CrossRef